Investigating the effects of home-based rehabilitation after intensive inpatient rehabilitation on motor function, activities of daily living, and caregiver burden. - Kenji Sato; Eri Otaka; Kenichi Ozaki; Kenta Shiramoto; Rie Narukawa; Takeshi Kamiya; Masaki Kamiya; Daiki Shimotori; Chiaki Kamizato; Naoki Itoh; Hitoshi Kagaya; Izumi Kondo (PLoS ONE)
Background Home-based rehabilitation involves professional rehabilitation care and guidance offered by physical, occupational, and speech therapists to patients in their homes to help them recuperate in a familiar living environment. The effects on the patient's motor function and activities of daily living (ADLs), and caregiver burden for community-dwelling patients are well-documented; however, little is known about the immediate benefits in patients discharged from the hospital. Therefore, we examined the effects of continuous home-based rehabilitation immediately after discharge to patients who received intensive rehabilitation during hospitalization. Methods We retrospectively reviewed 150 patients [mean (standard deviation, SD) = 81 (9) years] discharged from the convalescent rehabilitation and community-based integrated care wards undergoing tailored home-based rehabilitation for 6 months (provided by physical or occupational therapists: 1-2 sessions of 40-60 min each per week). The outcome measures at baseline and after 3 and 6 months were compared. Results The participants included in this study had orthopedic (n = 76), cerebrovascular (n = 50), neuromuscular (n = 11), cardiovascular (n = 5), respiratory (n = 3), cancer (n = 3) and other diseases (n = 2). The mean (SD) time from discharge to the start of rehabilitation was 4 (4) days. One-way analysis of variance and post-hoc comparisons showed significant improvements at 3 months from baseline in grip strength (p = 0.002), 5-repetition sit-to-stand test (p < 0.001), Standing test for Imbalance and Disequilibrium test (p = 0.025), Functional Independence Measure (p < 0.001), modified Frenchay Activities Index (p < 0.001). Additionally, a statistically significant improvement was observed in the Japanese Zarit Caregiver Burden Interview score at 6 months from baseline (p < 0.001). Conclusions Home-based rehabilitation improves motor function, ADLs, and instrumental ADLs even after intensive inpatient rehabilitation and decreases the burden of the caregiver in the long term. Hence, tailored home-based rehabilitation should be continuously implemented after the completion of intensive inpatient rehabilitation.